Strategi Penegakan Hukum Progresif untuk Mengembalikan Kerugian Negara dalam Tindak Pidana korupsi Melalui Pidana Uang Pengganti - Ade Mahmud (Faculty of Law, Andalas University, 2019)
The problems in payment of compensation for state’s loss in a verdict of corruption case factually raises injustice, because its implementation is hampered by the rules that give the convicted the opportunity to choose substitution punishment, that is prison punishment. This problem will cause the objective to recover the state loss due to corruption act will not be achieved. Therefore, there should a study on the policy regarding the punishment of compensation for state loss. This research is aimed: first, to find out the implementation of compensation of state losses in a corruption case, and the second is to find out a progressive legal strategy to recover the state losses through compensation punishment. This research finds that the implementation of the compensation punishment is not effective to recover the state's loss as a whole, because the judges has positivistic and compromise view and base their decision just on the formulation of article 18 paragraph (3) of Law No. 31 of 1999 concerning Corruption Eradication that gives opportunity for a convicted person to choose a substitution punishment instead of paying the compensation. The fact shows that the convicted person prefers to choose substitution punishment instead of paying the compensation. This will cause that the state loss cannot be recovered. The strategy to implement progressive law to recover the state losses through the payment of compensation can be done, first by confiscating the assets of the convicted since the beginning the investigation. The strategy will enable the prosecutor to find a breakthrough for the rigidness of written law and make possible for the prosecutor to confiscate the assets as long as one month after the verdict is due. The second strategy is by performing so-called contra-legal measures by imposing a compensation punishment based on Article 18 paragraph (1) b of Law No. 31 of 1999 concerning Eradication of Corruption and ignoring the provisions of Article 18 paragraph (3) that is without substitution punishment, but it must be preceded by a collateral confiscation of the convicted assets.